Silkworm Pupae Meal: A Breakthrough for Conventional Poultry Feed - Bipanchi Tamuly; S. Manimegalai; P. Chitra; P. Priyadharshini; K. Baranidharan (Archives of Current Research International, 2024)
The growing demand for cost-effective and sustainable poultry feed has spurred interest in alternative protein sources. This review explores the potential of silkworm pupae meal (SWPM) as a viable substitute for conventional protein sources such as soyabean and fish meal in poultry diets. Silkworm pupae, a by-product of the silk industry, are rich in crude protein (up to 80% in defatted meal) and essential amino acids, particularly lysine and methionine. These nutritional attributes, along with a high content of fatty acids, make SWPM an attractive ingredient for poultry feed. The paper discusses the environmental benefits of using silkworm pupae, which include reducing waste and mitigating the ecological impact of traditional feed ingredients. Additionally, the incorporation of SWPM in poultry diets has been shown to improve nutrient digestibility, feeding preferences, and gut health in chickens. This review highlights the promise of silkworm pupae meal as a sustainable and economical alternative in the poultry feed industry, offering a potential solution to the challenges of rising feed costs and environmental sustainability. Replacing the traditional protein sources such as soyabean meal & fish meal with silkworm pupae meal may break a chain of increasing feed costs and make a sustainable change towards a cost-effective feed. In this arena, silkworm pupae meal is a high-nutritional-value protein rich animal feed component, exceeding up to 50% crude protein content to over 80% at times. It contains methionine, lysine, chitin, and insoluble protein, possibly indicating fibre. Researchers have investigated in many ways how the use of full-fat and defatted silkworm pupae meal in chicken feed affects nutrient digestibility, feeding preferences and gut bacteria, with the aim of potentially substituting it for traditional protein sources in poultry diets.